Junior high drama ebook A graphic novel. - Simonson, Louise (2019)
Welcome to Memorial Middle School, where drama fills the classrooms and follows students home on the bus. Social awkwardness. Mean girls. Hallway gossip. It's all part of life in junior high, but maybe it helps to know you aren't alone. Can Lucia avoid the boy-girl party? Will Kamilla overcome her self-consciousness and try out for the play? Can Allie keep anyone from finding out her secret? Told in graphic formal, Junior High Drama shows that while you can't escape the drama, you can certainly survive it.